Single VDTA-Based Tunable Floating Lossy Inductance Simulation Circuits - Moonmuang, Pitchayanin; Tangsrirat, Worapong (My University, 2023)
In this study, two circuit topologies for simulating tunable lossy floating inductors are proposed. In each design, the simulators make use of a single voltage differencing transconductance amplifier (VDTA), and only two passive elements with a grounded capacitor. The proposed active inductance simulators do not need some kind of component matching conditions and cancellation constraints for the desired realization. Besides, the simulated equivalent resistance and inductance values are independently tunable through a single resistor and/or the transconductances of the VDTA. The workability of all the proposed circuits is well accomplished through PSPICE simulations and experimental test results. To ascertain the feasibility of the proposed inductor designs, they are used to construct a fourth-order equal-ripple (3-dB) lowpass filter and an electronically tunable sinusoidal oscillator.
Keywords: Inductance simulator; Lossy inductor; RL impedance; Voltage differencing transconductance amplifier (VDTA)